Dr. Leandro Castañón Roche (1925-2016) - Cobas Vilches, María Elena; Canto Pérez, Maritza; Márquez Rancaño, Ernesto (Revista Cubana de Estomatología, 2017)
On Tuesday, November 22, 2016, the distinguished professor Dr. Leandro Castañón Roche passed away at 91 years of age, an example of professionalism and revolutionary value, an unfortunate loss for Stomatology in the central region of Cuba. He was born in Placetas, municipality of the former province of Las Villas, the 1st. October 1925. He entered the University of Havana in 1944 to study Dentistry; during his life as a university student he excelled in baseball, he was a monitor (delegate at that time) of the subjects Operatory and General Pathology; in these years he collaborated with the Movimiento Union Revolutionary Insurrection that integrated the University Student Federation (FEU) of the School of Dentistry; his academic results were excellent. He graduated from the University of Havana on July 11, 1949 as a Doctor in Dental Surgery; He moved to Placetas and worked in the office with his father; next to him began his revolutionary activity after March 10 when Batista’s military coup; He was very active in clandestine work, as a member of the Revolutionary Directorate, the 26th of July Movement, the Authentic Organization, the Popular Socialist Party and the Insurrectional Nation Movement. At the triumph of the Revolution he held different responsibilities and encomiendas for the organization of the municipality in this new stage. In 1960 he was appointed Municipal Commissioner of Placetas; During this time he attended the National School "Ñico López" and participated in the Literacy Campaign in 1961. He was a member of the Provincial Party Bureau in Las Villas until 1968. His intellectual work was very active as of 1967: he began his first years in the postgraduate improvement since he is selected to receive a course of oral surgery at the National Institute of Stomatological Improvement (INPE), this represented a great start in the world of the Maxillofacial Surgery because in 1975 he graduated as an I Degree Specialist in Maxillofacial Surgery at the "Manuel Fajardo" Teaching Hospital in Havana. His specialty completion work was a lip reconstruction technique, created by him for patients affected by lip cancer, and later recognized as the Castañón technique. This was his top research because it links the oncological criterion and the plastic vision, with it he achieved recognition in important events and medical journals, he was distinguished by the scientific community and the State Council for his contribution to the sciences. Years later he obtained the II Degree of the specialty. He collaborated with the teaching that was given to students of the last year at the School of Stomatology of Havana. His teaching work continued in Placetas because he was responsible and teaching collaborator of technical students in Stomatology; later he directed the school of dental assistants in the province. In the Provincial Teaching Hospital of Villa Clara today "Celestino Hernández Robau", his intellectual work was on the rise: he was the founder of undergraduate and postgraduate teaching and stood out in the training of specialists from the three central provinces. In 1980 he was appointed head of the Maxillofacial Surgery service, he participated during his life in a large number of provincial and national events; He was a very prominent anirist, he started in this movement in 1976 as his life president in the aforementioned hospital, about this organization he expressed: "The ANIR is my life, I achieved good results ...". In 1981 he was selected Outstanding Innovator and in 1986 Vanguardia Nacional. Its innovations also include: an instrument for mandibular prognathism operations using the Caldwell Letterman technique (guide hook) and a technique for eyelid reconstruction. The teacher Castanon, as we call him his disciples, loved science and studied it with fidelity, longing and dedication; in correspondence with his dedication have been the results he achieved, he managed not only to put his name among the most outstanding innovators in the country, but the entities he represented have also enjoyed such prestige, which was reflected in the press reports of those years. He published several articles in different national and foreign journals, and supervised various works of completion of the specialty of Maxillofacial Surgery. He was an excellent teacher, creative, much admired and loved by his students who will always follow his example of altruistic educator pending to educate and educate the new student generations. In his private life he formed an excellent family, his filial relationship was admirable and his example made his daughter and grandson embrace the career of Medicine; the first as a plastic surgeon and the second as a legal doctor. There was an excellent atmosphere of harmony in his family nucleus and of devotion and admiration towards his person that will never be able to disappear even with the passage of time.